Ongole Crossbreeds conservation with the existence value approach and the willingness to pay farmers in Yogyakarta Indonesia - Elisa Christian Adhie Ernanto; Rini Widiati; Tri Anggraeni Kusumastuti (Livestock and Animal Research, 2022)
Objective: The objective of the research was to identify and measure the value of existence, thus to analyze Willingness To Pay of farmer to keep the existence of Ongole Crossbreeds.Methods: The research was conducted in the Independent Taruna Group, Ngemplak District, Sleman Regency with the consideration that it is a PO cattle group that has the largest number of members in Sleman Regency. Determination of respondents by census as many as 40 farmers. Data was collected through interviews using a questionnaire as a research instrument. The identification of the existence of the business includes the availability of inputs, the development of outputs and the accessibility of supporting PO cattle using a Likert scale. Testing the consistency of statement items is tested for validity and reliability. The Contingent Valuation method is used to estimate the Willingness to Pay of farmers in maintaining their business.Results: The value of business sustainability from the existence of input (0.896), output (0.985), and support (0.885) is in the high category. The largest WTP value is the purchase of young female cattle with an average value of IDR 14.500.000/head, followed by waste treatment of IDR. 11,509,000/year and parent insurance of IDR. 40,000/head/year. The aggregate value of the group's WTP is IDR. 1,350,000,000/year.Conclusions: Livestock groups can maintain the existence of PO cattle because of the support of business existence, utilization of dung waste to increase income, and Willingness To Pay farmers. On the other hand, government support to provide subsidies and Siwab or its extension Mandatory cattle breeding is maintained to maintain the presence of PO cattle